Efektivitas Glukosa dan Sukrosa Terhadap Peak Expiratory Flow Rate (PEFR) dan Daya Tahan Kardiovaskular - Arimbi Arimbi; Arifuddin Usman; Poppy Elisano Arfanda; Nur Fadly Alamsyah; Safaruddin Safaruddin (Seminar Nasional LP2M UNM, 2019)
This research to determine how the effect of glucose and sucrose on cardiovascular endurance and PEFR values and whether there is a difference in the effect of glucose and sucrose on cardio and PEFR endurance in the two groups of FIK UNM athletes. This type of research is a multigroup pretest-posttest design. The population of this study were 35 members of the FIK UNM futsal club, and the sample was 30 FIK UNM futsal athletes divided into 2 groups of 15 samples each, through a purposive random sampling technique. The results of this study showed that the mean VO2max in the group given sucrose before the test was 34.3 ml / kg / minute increasing in the post test by 39.4 ml / kg / minute while the mean VO2max in the group given glucose before the test was 35.8 ml / kg / minute decreasing in the post test it became 34.7 ml / kg / min, while the average PEFR in the group given sucrose before the test was 364 L / s increased in the post test by 416 L / s, while the average PEFR in the group given glucose before the test was 342 L / s sec also increased at the post test by 355.33 L / sec.